Tubular HIPK2 is a key contributor to renal fibrosis - Wenzhen Xiao; Jing E; Li Bao; Ying Fan; Yuanmeng Jin; Andrew Wang; David Bauman; Zhengzhe Li; Ya-Li Zheng; Ruijie Liu; Kyung Lee; John Cijiang He (JCI Insight, 2020)
We previously used global Hipk2-null mice in various models of kidney disease to demonstrate the central role of homeodomain-interacting protein kinase 2 (HIPK2) in renal fibrosis development. However, renal tubular epithelial cell–specific (RTEC-specific) HIPK2 function in renal fibrogenesis has yet to be determined. Here, we show that modulation of tubular HIPK2 expression and activity affects renal fibrosis development in vivo. The loss of HIPK2 expression in RTECs resulted in a marked diminution of renal fibrosis in unilateral ureteral obstruction (UUO) mouse models and HIV-associated nephropathy (HIVAN) mouse models, which was associated with the reduction of Smad3 activation and downstream expression of profibrotic markers. Conversely, WT HIPK2 overexpression in RTECs accentuated the extent of renal fibrosis in the setting of UUO, HIVAN, and folic acid–induced nephropathy in mice. Notably, kinase-dead HIPK2 mutant overexpression or administration of BT173, an allosteric inhibitor of HIPK2-Smad3 interaction, markedly attenuated the renal fibrosis in these mouse models of kidney disease, indicating that HIPK2 requires both the kinase activity and its interaction with Smad3 to promote TGF-β–mediated renal fibrosis. Together, these results establish an important RTEC-specific role of HIPK2 in kidney fibrosis and further substantiate the inhibition of HIPK2 as a therapeutic approach against renal fibrosis.